Análise do potencial imunomodulador de proteínas recombinantes do Schistosoma mansoni, no diabetes tipo 2 - Santos, Clara Louise Barreto Xavier dos (2024)
Type 2 diabetes mellitus (DM2) fits among diseases classified as metabolic syndrome, commonly associated with obesity and sedentary lifestyle. Furthermore, due to the modification in insulin action, DM2 leads to severe cases of hyperglycemia in the carrier, predisposing to pathological complications. Recently, research in the field has linked the development of the disease with an increase in pro-inflammatory markers, characterizing a low-grade chronic inflammation, mainly in adipose and hepatic tissues. Therefore, molecules with immunomodulatory potential have significant applicability in the therapeutic scope in controlling metabolic dysfunction associated with inflammation. Proteins derived from the parasite Schistosoma mansoni have been suggested as regulators of processes that can modify the functions of immune cells, reducing inflammation and improving glucose tolerance. As an example, in this work, two recombinant membrane proteins of S. mansoni, Sm14 and SmCyp, were analyzed for their immunomodulatory potential. Through cell viability analyses, cytokine quantification, flow cytometry, determination of reactive oxygen and nitrogen species, and imaging, the considerable immunomodulatory potential of such proteins was confirmed, with alteration/decrease in the synthesis of inflammatory cytokines in macrophages, as well as their polarization, increased cell viability, and alteration in the production of nitrogen reactive species when compared to the control group.